2021
DOI: 10.3390/ijerph18084069
|View full text |Cite
|
Sign up to set email alerts
|

Applying Machine Learning to Identify Anti-Vaccination Tweets during the COVID-19 Pandemic

Abstract: Anti-vaccination attitudes have been an issue since the development of the first vaccines. The increasing use of social media as a source of health information may contribute to vaccine hesitancy due to anti-vaccination content widely available on social media, including Twitter. Being able to identify anti-vaccination tweets could provide useful information for formulating strategies to reduce anti-vaccination sentiments among different groups. This study aims to evaluate the performance of different natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 34 publications
1
30
0
2
Order By: Relevance
“…Griffith et al (2021) have studied the COVID-19 vaccine hesitancy in Canada through the content analysis of tweets using the theoretical domains framework. With the aid of machine learning, To et al (2021) identify anti-vaccination tweets during the COVID-19 pandemic. Bonnevie et al (2021) examined the vaccine opposition shifts on Twitter, and themes were identified from Twitter posts.…”
Section: Review Of the Previous Literaturementioning
confidence: 99%
“…Griffith et al (2021) have studied the COVID-19 vaccine hesitancy in Canada through the content analysis of tweets using the theoretical domains framework. With the aid of machine learning, To et al (2021) identify anti-vaccination tweets during the COVID-19 pandemic. Bonnevie et al (2021) examined the vaccine opposition shifts on Twitter, and themes were identified from Twitter posts.…”
Section: Review Of the Previous Literaturementioning
confidence: 99%
“…The results are shown in Table 1. A similar work is used to predict the patients emotions by (To et al 2021) using the algorithms. (Bangyal et al 2021) On sparse and unstructured data, the Random Forest does not perform as well.…”
Section: Discussionmentioning
confidence: 99%
“…Crowdbreak is a digital platform utilising the stream filter API and was used in COVID-Twitter-BERT [81] , [82] . Tweepy [83] , is a popular Python package used to communicate with the Twitter API [84] , [85] , [86] . Rapid Miner is a tool that can also be used for clustering and classification [87] , [88] .…”
Section: Sentiment Analysismentioning
confidence: 99%